Pengaruh Pengetahuan Pajak,Pelaksanaan Relawan Pajak Dan Motivasi Karir Terhadap Minat Berkarir Mahasiswa Akuntansi Di Bidang Perpajakan - Yentina Siregar; Maria Silitonga; Hendri Jaya; Artiani Lestari Tiurmaida Manalu (MEASUREMENT : Jurnal Program Studi Akuntansi, 2024)
Abstract. This study's overarching goal is to dissect the impact of factors including tax literacy, tax volunteerism, intrinsic drive, and interest in taxation as a profession.When analyzing data, one may check for a correlation between two variables by using multiple linear regression. Knowledge of taxes significantly affects interest in a tax-related profession, according to the data. Furthermore, tax volunteers help increase interest in taxes as a profession.There was also a strong correlation between professional drive and a desire to work in taxes. Implications for future study and practice include raising awareness of tax issues, promoting tax-related volunteer work, and inspiring people to seek out tax-related job opportunities.